Soluble ST2 levels are associated with bleeding in patients with severe Leptospirosis. - Jiri F P Wagenaar; M Hussein Gasem; Marga G A Goris; Mariska Leeflang; Rudy A Hartskeerl; Tom van der Poll; Cornelis van 't Veer; Eric C M van Gorp (Public Library of Science (PLoS), 2009)
Severe leptospirosis features bleeding and multi-organ failure, leading to shock and death. Currently it is assumed that both exaggerated inflammation and immune suppression contribute to mortality in sepsis. Indeed, several proinflammatory cytokines are reported to be induced during leptospirosis. Toll-like receptors, which play an important role in the initiation of an innate immune response, are inhibited by negative regulators including the membrane-bound ST2 (mST2) receptor. Soluble ST2 (sST2) has been implicated to inhibit signaling through mST2. The aim of this study was to determine the extent of sST2 and (pro-) inflammatory cytokine release in patients with severe leptospirosis.In an observational study, 68 consecutive cases of severe leptospirosis were included. Soluble ST2 and cytokines (TNF-alpha, IL-1beta, IL-6, IL-8, and IL-10) were repeatedly measured. To determine whether blood cells are a source of sST2 during infection, we undertook an in vitro experiment: human whole blood and peripheral blood mononuclear cells (PBMC) were stimulated with viable pathogenic Leptospira. All patients showed elevated sST2, IL-6, IL-8, and IL-10 levels on admission. Admission sST2 levels correlated with IL-6, IL-8, and IL-10. Thirty-four patients (50%) showed clinical bleeding. Soluble ST2 levels were significantly associated with bleeding overall (OR 2.0; 95%CI: 1.2-3.6) and severe bleeding (OR 5.1; 95%CI: 1.1-23.8). This association was unique, since none of the cytokines showed this correlation. Moreover, sST2 was associated with mortality (OR 2.4; 95%CI: 1.0-5.8). When either whole blood or isolated PBMCs were stimulated with Leptospira in vitro, no sST2 production could be detected.Patients with severe leptospirosis demonstrated elevated plasma sST2 levels. Soluble ST2 levels were associated with bleeding and mortality. In vitro experiments showed that (white) blood cells are probably not the source. In this regard, sST2 could be an indicative marker for tissue damage in patients suffering from severe leptospirosis.